Sex Differences in the Associations of Obesity With Hypothyroidism and Thyroid Autoimmunity Among Chinese Adults - Wang, Bin; Song, Ronghua; He, Weiwei; Yao, Qiuming; Li, Qian; Jia, Xi; Zhang, Jin-an (Frontiers in Physiology, 2018)
There is an intensive link between obesity and thyroid dysfunction, but this relationship in Asians is still unclear. This study was conducted to define the impact of obesity on risk of hypothyroidism and thyroid autoimmunity among Chinese adults. A population-based, cross-sectional study was carried out, which enrolled a total of 2,808 Chinese adults. To assess the associations of obesity with hypothyroidism and thyroid autoimmunity, odds ratio (ORs) with 95% confidence intervals (95%CIs) were calculated through logistic regression model, and the correlations of body mass index (BMI) with TPOAb and TGAb were also analyzed. Obese females had higher risk of hypothyroidism (22.7% vs. 15.0%; OR = 1.66, 95%CI 1.10-2.53; P = 0.02) and higher risk of subclinical hypothyroidism (22.1% vs. 13.4%; OR = 1.83, 95%CI 1.20-2.80; P = 0.005) than non-obese females. Multivariate logistic regression analysis found significant associations of obesity with hypothyroidism (Adjusted OR = 1.54, 95%CI 1.00-2.38; P = 0.05) and subclinical hypothyroidism (Adjusted OR = 1.69, 95%CI 1.09-2.63; P = 0.02) in females after adjustment for confounding factors. No association between obesity and hypothyroidism was observed in male participants. Spearman's correlation analysis suggested BMI was significantly and positively correlated with TPOAb (Spearman's r = 0.062, P = 0.022) in men but not in women. Linear regression analysis suggested an obviously positive correlation of BMI with TPOAb in men (β = 0.018, P = 0.015) and an obviously negative correlation of BMI with TGAb in women (β = -0.025, P = 0.012), respectively. The study suggests sex differences in the associations of obesity with hypothyroidism and thyroid autoimmunity among Chinese adults. Further studies are needed to better understand the exact mechanism of sex difference in the obesity-thyroid relationship.